STRATEGI PENGEMBANGAN AGRIBISNIS BUAH NAGA DI PULAU BENGKALIS - Muhammad Faisal; Syaiful Hadi; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes this is to knowimplemantation of agribusiness systems dragonfruit developmentand design appropriate development strategies for its enterpreneurs bengkalis island. Analytical methods used in the study is descriptive and SWOT analysis. Results revealed that there were three subsystems that goed well: 1. Subsystem input supply, 2. Subsystem marketing, 3. Subsystem supply. The strategy for development by entrepreneur are: (i). Increase the total area of dragonfruit plants which aims to meet the needs of consumers and the market. (ii). Support joint development of dragonfruit by the district bengkalis. (iii). Participating role in the training of professionals in government or agribusiness development dragonfruit. (iv). Encourage the development of dragonfruit basedproduct that is able to create added value in the dragonfruit farm. Keywords: Agribusiness, DragonFruit, SWOT.